Discourse, Power, and Resistance Down Under
VIII, 213 p.
Keywords: This edited collection is an eclectic and provocative volume taken from presentations that reflect the scholarship of the inaugural AQR/ DPR Down Under conference that was held in Cairns in 2011 in Australia. This was a ground-breaking conference that brought together scholars, researchers and practitioners from across Australia, UK, Japan, Italy, Finland, New Zealand, Luxembourg, South Africa, Vietnam, Malaysia, Tanzania and Mexico. The theme of the conference represented at the conference and in this volume was that of: Politicizing Qualitative Research. Delegates presented papers that sought to challenge research practices that too often can delegitimize Other ways of knowing. Confronting, disrupting and resisting the epistemological ‘common sense’ way of doing research within the academy can be a risky business and is often a fraught and contested endeavor. However, as the papers in this volume illustrate, contestation promises opportunities for re-perceiving, re-interpreting, and productively disrupting the orthodoxies of disciplinarity. – ‘Many thanks to Ignacio Rojas whose patient assistance and expertise as an artist in designing the cover proved invaluable in bringing this book to print.’.